Movement Analysis Of Bedincak Gymnastics Based On Traditional Dance Of Bangka Belitung - Srilestari, Widia; Narawati, Tati; Sukmayadi, Yudi (Gondang: Jurnal Seni dan Budaya, 2024)
The problem of this research is how Senam Bedincak can be an alternative recreational sport for the people of Bangka Belitung. The purpose of this study is to describe and analyze the choreographic and musical structure of Bedincak Gymnastics in Bedindak Gymnastics so that it becomes an alternative recreational sport for the people of Bangka Belitung. The method used is descriptive analysis with a qualitative approach. Bedincak Gymnastics is a community sport that adopts traditional Bangka Belitung dance movements such as Kedidi Dance, Dincak Dambus Dance and Measles Dance. The purpose of Bedincak Gymnastics is to improve the overall health and fitness of the community as well as to introduce and preserve Bangka Belitung culture to the community. Bedincak Gymnastics consists of 7 movement structures, namely opening movement, pattern 1 movement, pattern string movement, bedincak basic movement, pattern 2 movement, pattern 3 movement and closing movement.